The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/rse2.138
|View full text |Cite
|
Sign up to set email alerts
|

Marmots from space: assessing population size and habitat use of a burrowing mammal using publicly available satellite images

Abstract: Social, burrowing mammals such as prairie dogs, ground squirrels or marmots are keystone species in grassland ecosystems. Grasslands have been converted into cropland or pastures globally, yet it remains virtually unknown how this has affected the biogeography of burrowing mammals, as efficient, broad‐scale survey methods are lacking. We aimed to test whether structures created by burrowing rodents can be reliably detected on publicly available, very‐high‐resolution satellite images, in order to assess rodent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…Burrows appear as bright spots in both historical and contemporary imagery due to the large amount of soil turned by the marmots when digging and tending to the burrow (figure 1). Burrow location validation with field visits suggested that no false negatives occurred [33]. False positives only occurred in recently abandoned colonies (where burrows are usually covered by darker vegetation than the surrounding areas), but these were extremely scarce in our study area [33].…”
Section: (C) Marmot Burrows and Their Spatial Distributionmentioning
confidence: 67%
See 4 more Smart Citations
“…Burrows appear as bright spots in both historical and contemporary imagery due to the large amount of soil turned by the marmots when digging and tending to the burrow (figure 1). Burrow location validation with field visits suggested that no false negatives occurred [33]. False positives only occurred in recently abandoned colonies (where burrows are usually covered by darker vegetation than the surrounding areas), but these were extremely scarce in our study area [33].…”
Section: (C) Marmot Burrows and Their Spatial Distributionmentioning
confidence: 67%
“…Other potential explanations for the high densities in croplands include a correlation between the most suitable marmot habitat and the suitable conditions for 'agriculture, a process locally described as 'colonies absorbed by agriculture' [51]. Indeed, our modelling results suggested that loamy soils had higher burrow densities compared to clayey or stony soils, which are less favourable for agriculture [33] (electronic supplementary material, S4). Finally, we caution that our study could not differentiate between grazed and ungrazed steppes, both combined in our single 'grassland' class.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations